Afterword - Bock, Zannie; du Toit, Marijke (Multilingual Margins: A journal of multilingualism from the periphery, 2024)
This Special Issue uses the African concept of ukuzilanda to reflect on the authors’ experiences of ‘becoming an academic’ at UWC. Central to this experience is the writing retreat, in particular one held inMay 2022, during which the authors engaged in a reflective writing session, which gave impetus to this volume.